Angiographic Characteristics and Treatment of Cervical Spinal Dural Arteriovenous Shunts - Kim, D.J.; Willinsky, R.; Geibprasert, S.; Krings, T.; Wallace, C.; Gentili, F.; terBrugge, K. (American Journal of Neuroradiology, 2010)
SUMMARY: Spinal DAVSs of the cervical level are rare lesions. The purpose of this study is to describe the clinical and angiographic characteristics of cervical spinal DAVSs. From a prospectively collected database including 449 cases of brain and spinal DAVSs, lesions located at the cervical level were selected. The clinical presentation, angiographic characteristics, and treatment outcome were assessed. Twelve cases of spinal DAVSs were identified at the level of the cervical spinal canal (male to female ratio = 8:4; mean age = 56.5 years). Five patients (41.7%) presented with hemorrhage including SAH (n = 4) and cerebellar hemorrhage (n = 1). Coincidental spinal DAVSs with cranial DAVSs or brain AVMs were noted in 5 cases (41.7%). The spinal DAVS was the symptomatic lesion in 10 cases and was incidentally discovered during evaluation for SAH from a coincidental lesion in 2 cases. Combined endovascular and surgical resection resulted in symptomatic improvement in 10 patients. In conclusion, DAVSs of the cervical spine are rare lesions which often present with hemorrhage and are frequently associated with complex coincidental vascular lesions. Combined endovascular and surgical treatment will result in good outcome. APAascending pharyngeal arteryASAanterior spinal arteryAVFarteriovenous fistulaAVMarteriovenous malformationbrbranchCaudcaudalCbllcerebellarCostoCervcostocervical arteryDAVSdural arteriovenous shuntDSAdigital subtraction angiographyFUfollow-uphemhemorrhageICAinternal cerebral arteryLtleftminminimalNAnot availablen-BCAn-butyl 2-cyanoacrylateOAoccipital arteryPVApolyvinyl alcoholRostrostralRtrightSCAsuperior cerebral arterySAHsubarachnoid hemorrhageSupPetSinsuperior petrosal sinusThCervthyrocervical arteryTsintransverse sinusVAvertebral artery